The development of institutional links to fight violence against women, Viçosa (MG) - Ferreira, Palloma Rosa; Bifano, Amelia Carla Sobrinho; Loreto , Maria das Dores Saraiva (Argumentum, 2021)
This article critically chronicles the development of institutional links between organisational sectors in fighting violence against women in Viçosa (MG), and the consequences of these links within the municipality from 2002 to 2019, with particular attention to their intensification from 2010 with the construction of the non-specialised Protective Network for the Care of Women in Situations of Violence. Documentary research was carried out using the official archives of the Interdisciplinary Nucleus of Gender Studies, the Casa das Mulheres programme and local and regional newspapers, as well as in-depth interviews with two actors from within the organisations. Despite the development of work to combat Violence against Women, there is a gap in relation to its institutionalisation within the public municipal arena, and there have been clearly verifiable setbacks.